Erosion Protection by Calcium Lactate/Sodium Fluoride Rinses under Different Salivary Flows in vitro - Borges, Alessandra B. [UNESP]; Scaramucci, Tais; Lippert, Frank; Zero, Domenick T.; Hara, Anderson T. (Karger, 2014)
This study investigated the effect of a calcium lactate pre-rinse on sodium fluoride protection in an in vitro erosion-remineralization model simulating two different salivary flow rates. Enamel and dentin specimens were randomly assigned to 6 groups (n = 8), according to the combination between rinse treatments - deionized water (DIW), 12 mm NaF (NaF) or 150 mm calcium lactate followed by NaF (CaL + NaF) and unstimulated salivary flow rates - 0.5 or 0.05 ml/min simulating normal and low salivary flow rates, respectively. The specimens were placed into custom-made devices, creating a sealed chamber on the specimen surface connected to a peristaltic pump. Citric acid was injected into the chamber for 2 min, followed by artificial saliva (0.5 or 0.05 ml/min) for 60 min. This cycle was repeated 4x/day for 3 days. Rinse treatments were performed daily 30 min after the 1st and 4th erosive challenges, for 1 min each time. Surface loss was determined by optical profilometry. KOH-soluble fluoride and structurally bound fluoride were determined in specimens at the end of the experiment. Data were analyzed by 2-way ANOVA and Tukey tests (alpha = 0.05). NaF and CaL + NaF exhibited significantly lower enamel and dentin loss than DIW, with no difference between them for normal flow conditions. The low salivary flow rate increased enamel and dentin loss, except for CaL + NaF, which presented overall higher KOH-soluble and structurally bound fluoride levels. The results suggest that the NaF rinse was able to reduce erosion progression. Although the CaL prerinse considerably increased F availability, it enhanced NaF protection against dentin erosion only under hyposalivatory conditions. (C) 2014 S. Karger AG, Basel
Keywords: Calcium; Dentin; Enamel; Erosion; Fluoride; Optical profilometry; Salivary flow rate